Peningkatan Profesionalisme Guru Melalui Organisasi Profesi dalam Mewujudkan Kualitas Pendidikan di Indonesia - Dwi Valentina Sihite; Elsa Prida Br Tarigan; Pebriana Asina Panjaitan; Sri Yunita (Pusat Riset dan Inovasi Nasional, 2024)
Education is an effort carried out by the government to educate society and advance the nation. Without professional teaching resources, the quality of education will not improve. The aim of this research is to determine the level of professionalism of teachers through professional organizations in achieving quality education, and obstacles to community development. A professional teacher/instructor cannot only be responsible for teaching materials in his field of knowledge, a professional teacher must have a broad understanding /in depth about human nature and society. The teaching profession has various professional attributes, one of which is the professional teacher organization, which was created to ensure the teaching profession can play a maximum role in the educational process and the quality of education. This research uses qualitative methods with a library study approach (Library Research)